Tooling for high speed machining - Mese, Peter; Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2003)
This program focuses on tooling balance and concentricity, carbide tools vs. indexable tooling, spindle interfaces, and high speed machining tooling misconceptions
Code no : DV03PUB72
Recorded at the High Speed Machining Technical Conference, Apr. 8 & 9, 2003, Itasca, Ill.
Title from title screen
Presenter: Peter Mese
Keywords: High-speed machining; Machining; Manufacturing processes